Islamic Criminal Law Study on The Seizure of Corruptor Assets as an Indonesian's Criminal Sanction in The Future - Syariful Alam; Yaris Adhial Fajrin; Sholahuddin Al-Fatih; Merve Ozkan Borsa (JURIS (Jurnal Ilmiah Syariah), 2022)
The current job transformation is one of the challenges for the state of Indonesia. Crimes over time have been carried out systematically, including corruption. The interesting thing about the development of efforts to combat corruption is the development of the concept of returning state finances. Legal entities in Indonesia have long experienced legal pluralism, as can be seen from the configuration of the community that carries out Islamic criminal law and customary law as local wisdom. This study uses a normative approach with secondary data support with the specification that the confiscation of corruptor's property in Islamic criminal law is divided into: Reproaches and reprimands/warnings, dismissing from his position (al-azl min al-wadzifah), by beating (whipping), punishment in the form of property (fines) and physical punishment, exile, crucifixion, death penalty. The relevance between these concepts is a form of legitimacy for the legal significance that comes from the beliefs and needs of the community. This article raises the concept of positive law with concepts in Islamic criminal law to find the relevance of the two which will later become part of the effort to function Islamic criminal law into Indonesian positive law in order to achieve the goal of a fair law and reduce corruption.